1993
DOI: 10.1111/j.1365-2672.1993.tb03033.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study of several enrichment broths for the detection of Salmonella spp. particularly in relation to water samples

Abstract: The selectivity and efficiency of several enrichment broths used for the the detection of salmonellas were comparatively evaluated under laboratory and environmental conditions. Media with selenite were less efficient in their inhibition of the growth of Gram-positive micro-organisms. Salmonellas grew slowly in tetrathionate broth and in media containing brilliant green. These media inhibited the growth of Salmonella typhi, which grew only in media containing selenite. The results obtained in the experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Paratyphi B isolate. The culture media we used is reported to inhibit growth of Salmonella serovars that cause typhoid or paratyphoid fever [ 50 ]. A study in Uganda reported S .…”
Section: Discussionmentioning
confidence: 99%
“…Paratyphi B isolate. The culture media we used is reported to inhibit growth of Salmonella serovars that cause typhoid or paratyphoid fever [ 50 ]. A study in Uganda reported S .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Salmonella sp. infections are detected by the isolation and identification of the bacteria from fecal cultures after several cultivation steps [4][5][6]. The identification is based on phenotypic and biochemical properties of the respective bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, if enough blood is cultured it may be possible to increase the sensitivity of blood culture to that of bone marrow culture, thus avoiding the need for bone marrow aspiration. For stool culture, enrichment media containing selenite have been shown to be more effective than other available enrichment media [13,14]. Selenite with mannitol (selenite M) has been recommended [15] but there have been no large-scale comparisons of different selenite containing enrichment broths.…”
Section: Introductionmentioning
confidence: 99%